爱德华•卡宾塔在西方与中国 ：以《中间之性》为中心 = Edward Carpenter "the intermediate sex" and its influence in Europe and China - 杨凯莉 Yong, Kai Li (2013)
本论文主要着重介绍爱德华•卡宾塔（Edward Carpenter，1844—1929）和他出版于1908年的作品《中间之性》。卡宾塔是十九世纪末至三十年代英国推崇同性恋爱及妇女解放的先驱，对当时的社会做出了不少得贡献。但对于卡宾塔的学术研究至今并未达到一个广泛的范围，当今中文学界也几乎并无存有关于卡宾塔的专题论文。因此本论文将要补充这个空隙，对卡宾塔的思想与著作进行研究，还原他对于同志解放和妇女解放的贡献，同时向读者介绍这位同性恋爱先驱。 全文共分为四章，第一章将进一步阐明本论文的研究动机与研究状态，说明本论文是在一篇提及到了卡宾塔在中国的翻译作品的论文为前提，展开了对于卡宾塔的研究，此论文也奠基了本论文的研究基础；第二章简要但斟酌地介绍卡宾塔的生平与他的作品《中间之性》，此节的极大部分内容都是从卡宾塔的传记以及《中间之性》的原文翻译成中文，向读者介绍这位同性恋爱先驱；第三章将简略论述欧洲的同性恋史，并同时介绍与卡宾塔拥有密切关系的知名作家 E.M 福斯特，以及从卡宾塔身上得到启发而创作的小说《莫瑞斯》；第四章要探讨卡宾塔思想的局限；最后第五章则整理出卡宾塔在中国的翻译作品，进一步叙述卡宾塔在中国的翻译作品和影响。 This thesis focuses on Edward Carpenter （1844—1929） and his work “The Intermediate Sex” which was published in 1908. Edward Carpenter is a pioneer in homosexual love and promoting women rights, however, there were not much attention given to him and his works in the modern academic sphere. Academic writings related to him were almost non-existent in the Chinese academic area. Hence, this thesis would like to fill up this gap in order to restore the works and contributions of Edward Carpenter and entice its readers to explore even more in depth into his life and thoughts. This thesis is largely translated from the original sources such as his biographies and his original works. This thesis consists of five main chapters. The first chapter further discusses the value of this research and the significance of this topic. The second chapter serves as an introduction of Edward Carpenter and his work “The Intermediate Sex”. Third chapter briefly recounts the homosexuality history in Europe and how Edward Carpenter plays a part in contribution to E.M Forster’s “Maurice”. The fourth chapter will review Carpenter’s thoughts and the last chapter discusses on his translated works in China, and his resonance in the country.